Value of FNAC in Diagnosis of Different Types of Thyroiditis and Its Comparison with Clinical and Biochemical Findings - Parveen, Kawser; Barua, AR; Hossain, A; Zaman, J; Momen, A (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):250-4. The abstract of this article is available on the PubMed website